Kajian Teknis dan Ekonomis dalam Merencanakan Penggantian Alat Angkut Lama dengan Alat Angkut Baru di Area Penambangan Andesit PT XYZ Kecamatan Cariu, Kabupaten Bogor, Provinsi Jawa Barat - Rizki Purnama; Noor Fauzi Isniarno (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. In its production activities, this company uses 1 unit of Caterpillar 345 GC excavation equipment which has been used for production for 2 years and 3 units of new Hino 500 New Ranger FM 260 JD production for 4 years. The condition of mechanical equipment that is classified as old and unfit for operation due to frequent breakdowns and requiring special maintenance and equipment operating costs are getting bigger, Of course it will affect productivity and production which will decrease. Therefore, so that the mining activities carried out are not disturbed due to equipment problems that often experience damage, it is necessary to replace the equipment. In planning the replacement of mechanical equipment, it is necessary to conduct a technical and economical study. For a technical study, it includes a study of equipment production, and for an economic study it includes operating costs, as well as ownership costs, Present Worth Cost value and Production Unit Cost value. Based on the results of a technical study, the digging tool has a work efficiency of 49.86% with a production of 271,384.18 BCM/Year and the old conveyance has a work efficiency of 86.03 % with a production of 270,996.93 BCM/year, As for the new means of transportation, it has a work efficiency of 86.95% with a production of 305409,91 BCM/Year. Based on the results of the economic study, it was found that the operating costs of the old conveyances were Rp 621,884,172.20 /year, and for the operating costs of the new conveyances, it was Rp 552,566,994.26 /year. In addition, the results of the calculation of Production Unit Cost for old transportation equipment are also obtained, which is Rp 3,100.46/BCM, while for new means of transport it is Rp 2,585.07/BCM. Abstrak. Dalam kegiatan produksinya perusahaan ini menggunakan alat gali-muat Caterpillar 345 GC sebanyak 1 unit yang telah digunakan untuk produksi selama 2 tahun, 3 unit alat angkut baru Hino 500 Ranger FM 260 JD baru yang sudah beroperasi selama 4 tahun. Kondisi dari alat mekanis yang sudah tergolong tua dan tidak layak beroperasi karena sering terjadi kerusakan dan membutuhkan perawatan yang khusus dan biaya operasi alat semakin besar, tentunya mempengaruhi produktivitas dan produksi yang akan semakin menurun. Oleh karena itu agar kegiatan penambangan yang dilakukan tidak terganggu karena masalah alat yang sering mengalami kerusakan maka perlu dilakukan penggantian alat. Dalam merencanakan penggantian alat mekanis maka perlu dilakukan kajian secara teknis dan ekonomis. Untuk kajian teknis meliputi kajian produksi alat, serta untuk kajian ekonomi meliputi biaya operasi, biaya kepemilikan, nilai Present Worth Cost serta nilai Production Unit Cost. Berdasarkan hasil kajian teknis, alat gali-muat mempunyai efisiensi kerja 49,86% dengan produksi sebesar 271.384,18 BCM/Tahun dan alat angkut lama mempunyai efisiensi kerja 86,03% dengan produksi sebesar 270.996,93 BCM/Tahun, Sedangkan untuk alat angkut baru mempunyai efisiensi kerja 86,95% dengan produksi sebesar 305.409,91 BCM/Tahun. Berdasarkan hasil kajian ekonomi didapatkan hasil biaya operasi alat angkut lama sebesar Rp 621.884.172,20 /tahun, dan untuk biaya operasi alat angkut baru adalah sebesar Rp 552.566.994,26 /tahun. Selain itu didapatkan juga hasil perhitungan Production Unit Cost alat angkut lama yaitu sebesar Rp 3.100,46/BCM, sedangkan untuk alat angkut baru yaitu sebesar Rp 2.585,07/BCM.